Validation of mitochondrial localization and essentiality of prioritized proteins assigned to the tripartite attachment complex in the protozoan parasite Trypanosoma brucei - Bittner, Jacqueline (Jihočeská univerzita, 2022)
During this thesis the localization of the prioritized proteins Tb927.11.13600, Tb927.11.14570, Tb927.4.840 and Tb927.6.4540 and their connection to the tripartite attachment complex of the protozoan parasite Trypanosoma brucei was examined to verify previous annotations found on the TrypTag database. Additionally, the essentiality of the prioritized proteins was evaluated.
Validation of mitochondrial localization and essentiality of prioritized proteins assigned to the tripartite attachment complex in the protozoan parasite Trypanosoma brucei
Keywords: Trypanosoma brucei; tripartite attachment complex; mitochondrion; putative protein; Tryptag; parasite; protein essentiality; protein localization; endogenous tagging; RNA interference; Trypanosoma brucei; tripartite attachment complex; mitochondrion; putative protein; Tryptag; parasite; protein essentiality; protein localization; endogenous tagging; RNA interference